Characteristics of Dermatological Manifestations in COVID-19 Patients - Dr. Jihan Hamodi Mahdi; Dr. Saba Ali Rashid (Academic Journal of Clinicians, 2023)
The COVID-19 pandemic outbreak is commonly presented with pulmonary manifestations. The skin lesions are recently regarded as common extra-pulmonary manifestations of the disease. This study aimed to characterize the cutaneous manifestations in COVID-19 patients and identifying the specific lesions and the underlying cause. This study was an observational cross sectional study implemented in the COVID-19 wards of Rozhawa Emergency hospital, outpatient clinics and COVID-19 wards of Rizgay Teaching hospital, outpatient clinics of Dermatology Teaching center and private clinics of Dermatology and Internal Medicine in Erbil city-Kurdistan region/Iraq through a period of six months from 1st of January to 30th of June, . on sample of 100 COVID-19 patients with skin manifestations. Results of the study showed that COVID-19 skin manifestations was mainly after the disease (54%). The common skin manifestation of COVID-19 disease was hair loss (29%), followed by; urticaria (17%), acne (10%) and skin erythema (10%). The onset of skin manifestations was related to age of patients and severity of COVID-19 disease. Types of skin manifestations were related to gender of patients, severity of COVID-19 disease and onset of skin manifestations. In conclusions: the common dermatological manifestations of COVID-19 disease were hair loss, urticaria, acne and skin erythema with predominance of late presentation. The types of skin lesions and the onset of presentation are affected by severity of COVID-19 disease.